2013
DOI: 10.1371/journal.pone.0081574
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cells in Patients with Venous Thromboembolism and Myeloproliferative Neoplasms

Abstract: BackgroundCirculating endothelial cells (CEC) may be a biomarker of vascular injury and pro-thrombotic tendency, while circulating endothelial progenitor cells (CEP) may be an indicator for angiogenesis and vascular remodelling. However, there is not a universally accepted standardized protocol to identify and quantify these cells and its clinical relevancy remains to be established.ObjectivesTo quantify CEC and CEP in patients with venous thromboembolism (VTE) and with myeloproliferative neoplasms (MPN), to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 61 publications
(77 reference statements)
0
19
0
11
Order By: Relevance
“…[6][7][8] Studies have found that the circulating endothelial cells in the blood of patients with PV are signi cantly higher than those in the normal control group, and their levels may also represent the degree of endothelial cell damages and disease progression. [8,9] Therefore, the vascular endothelial cells of patients with PV are damaged. Healthy endothelial cells can inhibit the activation of platelets, and when endothelial cells are damaged, it can promote the thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Studies have found that the circulating endothelial cells in the blood of patients with PV are signi cantly higher than those in the normal control group, and their levels may also represent the degree of endothelial cell damages and disease progression. [8,9] Therefore, the vascular endothelial cells of patients with PV are damaged. Healthy endothelial cells can inhibit the activation of platelets, and when endothelial cells are damaged, it can promote the thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Il contribue à l'inhibition de l'adhérence des plaquettes et de l'activation de la coagulation. Au cours des néoplasies myéloprolifératives, plusieurs observations sont en faveur de l'existence d'une activation du compartiment endothélial : augmentation des taux circulants de thrombomoduline [27], de facteur von Willebrand (vWF) [27], de sélectines (E-et P-sélectine) [44], et de cellules endothéliales circulantes [45]. Acteur majeur de la vasorelaxation, l'oxyde nitrique (NO) est produit en moindre quantité par les cellules endothéliales de patients présentant une thrombocytémie essentielle [46].…”
Section: Le Rôle Des Leucocytesunclassified
“… 72 , 73 CD142 (tissue factor), CD62P (P-selectin), and CD62E (E-selectin) are among the most common CD markers expressed following the activation of endothelial cells, which mediate the adhesion of platelets to these cells. 74 Furthermore, the increased expressions of intercellular and vascular adhesion molecules (including CD54 and CD106) on these cells, which play a role in the leuko-endothelial adhesion, might contribute to the prognosis of thrombotic events in JAK2 V617F positive disorders ( Table 1 ). 52 , 74 …”
Section: Markers Of Circulating Endothelial Cells and Activation Omentioning
confidence: 99%
“… 74 Furthermore, the increased expressions of intercellular and vascular adhesion molecules (including CD54 and CD106) on these cells, which play a role in the leuko-endothelial adhesion, might contribute to the prognosis of thrombotic events in JAK2 V617F positive disorders ( Table 1 ). 52 , 74 …”
Section: Markers Of Circulating Endothelial Cells and Activation Omentioning
confidence: 99%